1997
DOI: 10.1007/s11606-006-5082-9
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of Physicians and Their Patients for End-of-Life Care

Abstract: OBJECTIVE:Both physicians and patients view advance directives as important, yet discussions occur infrequently. We assessed differences and correlations between physicians' and their patients' desires for end-of-life care for themselves. MEASUREMENTS AND MAIN RESULTS:Study physicians ( n ‫؍‬ 78) were residents and faculty practicing in an inner-city, academic primary care general internal medicine practice. Patients ( n ‫؍‬ 831) received primary care from these physicians and were either at least 75 or betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 27 publications
(39 reference statements)
1
38
0
Order By: Relevance
“…Finally, it was observed that African American patients preferred more aggressive treatment than white patients in the event of terminal illness. 16 It may be inferred from these observations that terminally ill patients who place a greater emphasis on quality of life are more likely to have a DNR order than those who place a greater emphasis on quantity of life. Accordingly, it is also assumed that patient's DNR status itself is a measure of degree to which one prefers aggressive medical interventions.…”
Section: Attitudinal Dispositionmentioning
confidence: 99%
“…Finally, it was observed that African American patients preferred more aggressive treatment than white patients in the event of terminal illness. 16 It may be inferred from these observations that terminally ill patients who place a greater emphasis on quality of life are more likely to have a DNR order than those who place a greater emphasis on quantity of life. Accordingly, it is also assumed that patient's DNR status itself is a measure of degree to which one prefers aggressive medical interventions.…”
Section: Attitudinal Dispositionmentioning
confidence: 99%
“…4 However, national prevalence of inpatient palliative care programs among community provider hospitals is 29%. 5 These programs have been shown to be effective in improving patient outcomes, including satisfaction, pain relief, and care concordance with patient preferences, [5][6][7][8][9][10][11][12] as well as leading to significant reductions in acute care service use. 13 Furthermore, recent studies have documented cost savings associated with the implementation of these consultative teams.…”
Section: Introductionmentioning
confidence: 99%
“…Though investigation of racial and ethnic variation in the utilization of surgical procedures and in access to primary care has provided important insights into inequities in the current delivery system, [4][5][6][7][8][9][10][11][12] relatively few studies have examined racial variation in the use of DNR orders. Moreover, prior studies largely focused on patient preferences for endof-life care and often involved small sample sizes, [13][14][15] single institutions, 14,16 or highly selected patient populations, 13,15,[17][18][19][20][21][22] raising questions about their generalizability. In addition, some larger studies involved patients hospitalized prior to the Patient Self-Determination Act, 23,24 and thus, may not be representative of current practice.…”
mentioning
confidence: 99%